Integration of the cloud computing paradigm with the opeerator network’s infrastructure - Soares, João Monteiro (2015)
The proliferation of Internet access allows that users have the possibility to use services available directly through the Internet, which translates in a change of the paradigm of using applications and in the way of communicating, popularizing in this way the so-called cloud computing paradigm. Cloud computing brings with it requirements at two different levels: at the cloud level, usually relying in centralized data centers, where information technology and network resources must be able to guarantee the demand of such services; and at the access level, i.e., depending on the service being consumed, different quality of service is required in the access network, which is a Network Operator (NO) domain. In summary, there is an obvious network dependency. However, the network has been playing a relatively minor role, mostly as a provider of (best-effort) connectivity within the cloud and in the access network. The work developed in this Thesis enables for the effective integration of cloud and NO domains, allowing the required network support for cloud. We propose a framework and a set of associated mechanisms for the integrated management and control of cloud computing and NO domains to provide endto- end services. Moreover, we elaborate a thorough study on the embedding of virtual resources in this integrated environment. The study focuses on maximizing the host of virtual resources on the physical infrastructure through optimal embedding strategies (considering the initial allocation of resources as well as adaptations through time), while at the same time minimizing the costs associated to energy consumption, in single and multiple domains. Furthermore, we explore how the NO can take advantage of the integrated environment to host traditional network functions. In this sense, we study how virtual network Service Functions (SFs) should be modelled and managed in a cloud environment and enhance the framework accordingly. A thorough evaluation of the proposed solutions was performed in the scope of this Thesis, assessing their benefits. We implemented proof of concepts to prove the added value, feasibility and easy deployment characteristics of the proposed framework. Furthermore, the embedding strategies evaluation has been performed through simulation and Integer Linear Programming (ILP) solving tools, and it showed that it is possible to reduce the physical infrastructure energy consumption without jeopardizing the virtual resources acceptance. This fact can be further increased by allowing virtual resource adaptation through time. However, one should have in mind the costs associated to adaptation processes. The costs can be minimized, but the virtual resource acceptance can be also reduced. This tradeoff has also been subject of the work in this Thesis.